Assessing Thermal Comfort and Indoor Air Quality: In an Educational Facility of a Semi-Arid Climate Zone - Kemalettin Parmaksiz; Mehmet Irfan Yesilnacar; Abdullah Izzeddin Karabulut (Atmosphere, 2024)
There are three main approaches to human thermal comfort; a psychological approach, a thermo-physiological approach, and an approach based on human energy balance. According to the ISO 7730 and ASHRAE Standard 55-2023 standards, the psychological approach defines thermal comfort as a mental state in which individuals feel satisfied with their surrounding environment. According to this definition, thermal comfort is very subjective and may vary between individuals, as well as according to the environment and climate. This study aimed to evaluate the thermal comfort levels of students in primary and high school classrooms situated within the semi-arid climatic conditions of Şanlıurfa. For this purpose, 15 Temmuz Şehitleri Secondary School, Kadir Evliyaoğlu College, and TOBB Science High School in Şanlıurfa were chosen as fieldwork locations. Within the scope of the study, the climatic conditions (classroom temperature, air velocity, humidity, radiant temperature, Tw, Tg carbon dioxide) were measured, and how the students felt under the thermal conditions of these classrooms was evaluated. The study encompasses both the heating season (winter) and the non-heating season (summer). Based on the findings obtained from the study, PMV (Predicted Mean Vote) and PPD (Predicted Percentage Dissatisfied) values and whether they are suitable thermal comfort for the people in these places tried to be determined by mathematical modeling and standards such as ASHRAE Standard 55-2023. While PMV values ranged between −0.58 (North) and 2.53 (East+South+West), PPD values were observed between 5% (South and some North facades) and 94% (East+South+West). While the South facade offers values close to the comfort range of 0.01–0.02 in terms of PMV, the East+South+West facade shows serious thermal discomfort with a PMV value of 2.53 and a PPD value of 94%.